Taxonomic Significance of Anatomical Characters in Some Species of Brassicaceae family in Iraq - Omer Qader , Karzan (University of Thi-Qar Journal of Science, 2019)
This paper elaborated transverse sections of leaves and stems of nineteen species belongs to 18 genera of Brassicaceae family. Anatomical characteristics were important in separation of taxa. The presence or absence of Collenchyma, Chlorenchyma and Pith, Mesophyll structure and epidermal surface were found to be important characters for the identification of Brassicaceae species. Two types of mesophyll have been recognized, dorsiventral (Bifacial) found in Sinaps alba L., Biscutella didyma L., Sameraria stylophora(Jaub. et Sp.) Boiss., Drabopsis nuda (Bel.) Stapf., Eruca sativa Mill., Capsella bursa-pastoris (L.) Medic., Calepina irregularis(Asso)Thell., Diplotaxis harra (Forssk.) Boiss., Sinapis arvensis L. and Nasturtium officinale R.Br. and isobilateral in the remaining species. Transverse sections of the midrib showed that most of species contains one vascular plants in all the species except Brassica oleracea L., Cheiranthus cheiri L., Crambe orientalis L., Draba bruniifolia Stev. and Sinaps alba L. which contains (1-3) vascular bundles. Collenchyma tissue present only in Diplotaxis harra, sinaps alba, Drabopsis nuda (Bel.) Stapf. Camelina rumelica, Cramba orientalis L., Cheiranthus cheiri L. and Cardaria drab Thell, it was higher in Cardaria drab was (150.50) um and lower in Crambe orientalis was (18.75) um. A diagnostic key based on combined stem and leaf were presented.